Spin the Windmill, Move the Culture: A STEAMS Innovation for Grade 3 through the KINCAR PUSADA Project - Marianah, Dina; Sumarmi, Sumarmi; Rahayuningsih, Sri; Kusumaningrum , Shirly Rizki; Mardatillah, Mardatillah (Papanda Publisher, 2025)
Twenty-first-century education demands integrative pedagogical approaches that develop students' holistic competencies while preserving cultural heritage. However, STEAMS implementation in Indonesian primary schools often lacks meaningful connections to local contexts, diminishing relevance and engagement. This study examined the effectiveness of the KINCAR PUSADA project—a culturally integrated STEAMS learning model—in developing multidimensional competencies and cultural awareness among third-grade elementary students. Classroom Action Research was conducted over two cycles at SD Negeri Klampok II, Probolinggo Regency, involving 19 third-grade students. Data were collected through structured observations, semi-structured interviews, STEAMS project assessment rubrics, and documentation. Analysis employed both qualitative thematic analysis and descriptive quantitative methods. The project demonstrated substantial improvements across all competency dimensions: 84.2% of students achieved autonomous problem-solving capabilities, creativity scores averaged 90/100, collaboration reached 88%, and communication attained 80%. Overall, 89.5% of students exceeded mastery criteria with a mean achievement score of 87.2. Students showed dramatic gains in renewable energy understanding (15.8% to 78.9%) and cultural awareness (31.6% to 84.2%). The KINCAR PUSADA project effectively integrates STEAMS competencies with cultural appreciation through authentic, contextual learning experiences. This model offers a replicable framework for implementing the Merdeka Curriculum's objectives while addressing the contextualization gap in Indonesian primary education.